1988
DOI: 10.1093/oxfordjournals.eurheartj.a062560
|View full text |Cite
|
Sign up to set email alerts
|

Left atrial ball thrombus: Echocardiographic features and clinical implications

Abstract: The echocardiographic features of left atrial ball thrombus associated with mitral stenosis are reviewed, and some previously unpublished cross-sectional echocardiographic findings presented. In one patient who had a large free-floating ball thrombus there was variation in its echocardiographic appearance; the thrombus was removed uneventfully at surgery. In another patient who had a pedunculated but immobile ball thrombus, a stalk was identified which attached it to the inter-atrial septum; this patient died … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
19
0

Year Published

1990
1990
2013
2013

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(19 citation statements)
references
References 0 publications
0
19
0
Order By: Relevance
“…Ball thrombi are thought to originate as small mural thrombi, usually on the interatrial septum, but rarely in the left atrial appendage [4]. In the present case the mural thrombus enlarged, forming a projecting mass attached by a pedicle to the atrial appendage wall.…”
Section: Discussionmentioning
confidence: 53%
See 1 more Smart Citation
“…Ball thrombi are thought to originate as small mural thrombi, usually on the interatrial septum, but rarely in the left atrial appendage [4]. In the present case the mural thrombus enlarged, forming a projecting mass attached by a pedicle to the atrial appendage wall.…”
Section: Discussionmentioning
confidence: 53%
“…Since then, several criteria for the diagnosis of a true ball thrombus have been proposed, all of which include the presence of a pedicle as an exclusion criterion. The distinction between true ball thrombi and other large spherical thrombi in the LA is purely academic [4].…”
Section: Introductionmentioning
confidence: 99%
“…9 Fraser et al reported a case of sudden death because of the detachment of an immobile LA thrombus following the initiation of anticoagulant therapy. 10 Sometimes, spontaneous severance of the stalk of a pedunculated thrombus in the LA might occur and this severed thrombus could block the mitral orifice and result in sudden death. 11 …”
Section: Is the Thrombus Organized?mentioning
confidence: 99%
“…Their presence should be consid ered in patients with mitral stenosis and atrial fibrilla tion who present syncope [2], It is also reported that an exacerbation of the neurologic symptoms could be re lated to postural changes [3], Nevertheless, even if many semeiological signs have been described to be associated with this entity, it is evident that two-dimensional echo cardiography is the technique of choice for the exact diagnosis. In fact, M-mode echocardiography lacks spec ificity [4], Recently, it has been described, as a typical sign of freely moving thrombi, the presence of changing échocardiographie appearance of the mass like a solid or cystic structure, depending on the different orientation of the internal sedimentations in relation to the echo sources due to the movement of the mass itself [4], In the case we report, different échocardiographie appearances, changing from a cystic structure to a solid mass, have been noted. Considering also the macroscopic aspect of the thrombus observed in our patient, like that described by Freser et al [4], we believe that the changing échocar diographie appearance should be considered a pathogno monic sign of ball thrombus; in fact, the association of these signs with the presence of mitral stenosis makes the diagnosis of atrial myxoma very unlikely.…”
mentioning
confidence: 99%
“…In fact, M-mode echocardiography lacks spec ificity [4], Recently, it has been described, as a typical sign of freely moving thrombi, the presence of changing échocardiographie appearance of the mass like a solid or cystic structure, depending on the different orientation of the internal sedimentations in relation to the echo sources due to the movement of the mass itself [4], In the case we report, different échocardiographie appearances, changing from a cystic structure to a solid mass, have been noted. Considering also the macroscopic aspect of the thrombus observed in our patient, like that described by Freser et al [4], we believe that the changing échocar diographie appearance should be considered a pathogno monic sign of ball thrombus; in fact, the association of these signs with the presence of mitral stenosis makes the diagnosis of atrial myxoma very unlikely.…”
mentioning
confidence: 99%